2009
DOI: 10.1136/vr.165.21.623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the administration of oxytocin or carbetocin to dairy cows at parturition on their subsequent fertility

Abstract: A total of 501 dairy cows were allocated sequentially to be treated immediately after parturition with either 25 iu oxytocin or 35 mg carbetocin, or to be left untreated. Any abnormal parturition, including assisted calving, the birth of twins or dead calves, retained fetal membranes or hypocalcaemia, was recorded, and the cows were examined between 28 and 42 days after calving for endometritis. Pregnancy was diagnosed from 30 days after insemination. The incidence of endometritis was similar (14 per cent, 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Reproductive tract disease may substantially impair performance [15, 23, 46]. Delay in uterine involution significantly affects fertility and reproductive performance [5, 9, 18, 39, 45]. Treatments that enhance or accelerate uterine involution, or reduce the incidence of uterine disease may increase reproductive efficiency.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Reproductive tract disease may substantially impair performance [15, 23, 46]. Delay in uterine involution significantly affects fertility and reproductive performance [5, 9, 18, 39, 45]. Treatments that enhance or accelerate uterine involution, or reduce the incidence of uterine disease may increase reproductive efficiency.…”
mentioning
confidence: 99%
“…Treatments that enhance or accelerate uterine involution, or reduce the incidence of uterine disease may increase reproductive efficiency. It has been suggested that ecbolic drugs like oxytocin and prostaglandin F2α (PGF2α) could be used as preventative treatments to enhance uterine involution by promoting uterine contraction and clearance of debris and fluid, and potentially improve reproductive performance [2, 5]. The normal bovine uterus shows a progressive decrease in contractility over time postpartum [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Red and blue symbols indicate data from the UK and the present study, respectively. Each symbol represents data from different studies in different years; the hatched line depicts a linear trend‐line for all data within each panel (Muller and Owens 1974, Philipsson 1976, Cobo‐Abreu and others 1979, Sandals and others 1979, Shanks and others 1979, Zamet and others 1979, Erb and others 1981a, Erb and others 1981b, Dohoo and Martin 1984, Erb and others 1985, Etherington and others 1985, Halpern and others 1985, Martin and others 1986, Hamudikuwanda and others 1987, Francos and Mayer 1988, Holt and others 1989, Lee and others 1989, Oltenacu and others 1990, Barkema and others 1992, Van Werven and others 1992, Harman and others 1996, Dematawena and Berger 1997, Domecq and others 1997, Kaneko and others 1997, Markusfeld and others 1997, Emanuelson and Oltenacu 1998, Suriyasathaporn and others 1998, Leblanc and others 2002, Esslemont and Kossaibati 2002, Barrett and others 2009 )…”
Section: Discussionmentioning
confidence: 99%
“…Early postpartum dairy cows treated with carbetocin had a lower occurrence of RFM (Kudlac and Zamecnik 1984). However, Barrett et al (2009) concluded that routine administration of a single injection of either oxytocin or carbetocin after calving had no significant benefit. (1989) reported the positive effects of PGF 2α on selected reproductive parameters in cattle.…”
Section: Discussionmentioning
confidence: 99%